Hegel, Marx, and the Necessity and Freedom Dialectic Marxist-Humanism and Critical Theory in the United States - Rockwell, Russell (Political Philosophy and Public Purpose,, 2018)
This book provides close readings of primary texts to analyze the linkage between G.W.F. Hegel's philosophy and Karl Marx's critical social theory of necessity and freedom. This is important for three reasons: first, to understand the significance of the changing relationships of work, society, and critical social theory in the origins of Hegelian-Marxism in the US, as documented in the recently published correspondence between the Marxist-Humanist theoretician Raya Dunayevskaya and the critical theorist Herbert Marcuse; second, to identify the intersections of the Critical Theorists Jurgen Habermas' and Marcuse's influential reinterpretations of Marx's "value theory" of economy and society that enables navigation of the changing relationships of the social and economic spheres in the last century, as developed in Marx's Grundrisse; and, thirdly, to assess the potential of Moishe Postone's renewal of Marx's value theory, largely conceived by the notion of a necessity and freedom dialectic intrinsic to capitalism.